Parasites as Biological Tags in Aquatic Hosts - Timi, Juan Tomas (2025)
Extant host-parasite associations are the result of tight reciprocal adaptations that allow parasites to exploit specifc biological features of their hosts. Due to the intimacy of their relationships, parasites may provide important ecological information on their host’s individuals, populations, communities, and even ecosystems, with their variability in any dimension of the host niche being interpretable as an indicator of such changes. This chapter compiles and updates the published research on parasites as indicators of ecological and distributional patterns and processes of their hosts and environments, mostly from the perspective of fsheries, which has promoted this methodology the most. These patterns are discussed at spatial and temporal scales. The rationale for using parasites as biological tags and the routine statistical techniques used are analysed, along with the criteria for the selection of suitable parasite tags, and their advantages and limitations in light of recent research, including that on non-teleost hosts. Those host traits affecting the use of parasite tags are also considered together with the increasingly recognised necessity for integrative multidisciplinary studies on fsh parasites, combining both classical methods and modern techniques. The analysis is extended to the use of parasite genetics as a source of data on spatial and temporal distribution of hosts. Finally, the scope of the methodology is extended from the level of host populations to host communities and biogeography, with application for ecosystem approaches to fsheries management and conservation of resources, respectively.